SISTEM PEMBELAJARAN TAHFIDH AL-QUR’AN DI PONDOK PESANTREN: STUDI NATURALISTIK DI MADRASAH ALIYAH AT-TAQWA UJUNG HARAPAN BEKASI - Kiki Zakiyah, Neng; Khoir HS, Abdul (Turats, 2016)
The aim of this research is to analyse on the learning system of the memorization of Qur?an in the Islamic Boarding School: A Naturalistic Study in the Islamic SeniorHigh School (Madrasah Aliyah) At-Taqwa Bekasi. The result of this research revealed that the subject of the memorization of Qur?an (tahfidz) has become of the formalsubjects taught once a week. In the process of the memorization of the Qur?an, the students use some various methods: the wahdah (the only one) method (memorizing verse one by one), the sima?i (the listening) method (listening and understanding the recitation of Qur?an), the method of memorizing 1-3 pages of the Qur?an a day, and the common repetition method. The implementation of learning system of the memorization of the Qur'an in the Islamic Boarding School (Pondok Pesantren) At-Taqwa is done once a week. The subjects of the memorazitation of the Qur?an taught include some aspects such as makhorij al-huruf (the source of Arabic letters), tajwid (the proper pronunciation for correct recitation of the Qur?an), the memorization deposit. The way of depositing memorization of the Qur?an used by the students is that every student comes forward the class to express his/her memorazion according to the memorization program of each student.